Provider perspectives of the complexities to abnormal mammography follow-up - Fair, Alecia M. (J Am Coll Radiol, 2017)
PURPOSE: This study explores provider perspectives on follow-up of abnormal mammography results in medically underserved patients. METHODS: We employed Yin’s Five-Phased Cycle of analysis to identify major themes drawn from interviews with breast health center providers. RESULTS: A linked patient tracking surveillance system, acknowledgement of Hispanic patients naming customs in the medical records at registration and innovative outreach strategies were revealed as approaches to improving diagnostic mammography follow-up. CONCLUSIONS: The test result management system emerged as major area for improvement at this hospital. A public hospital brings unique delivery of care challenges. A facility-tailored approach complimenting mammography follow-up guidelines may be advisable.